Crow (Corvus spp.) meat: research possibilities to determine nutritional quality and health risks - Jaime A. Teixeira da Silva (Nutrimentum et Curae)
There is very limited (if any) literature on the potential use of corvids, specifically crows, as game meat. Despite the worldwide presence of corvids (including crows), especially in urban and other anthropogenic settings, a negative perception of this proposal might arise due to their scavenging of carcasses and waste. In some cases, diseases are present in crow meat, but assessments are still not widespread. This perspective proposes crow meat as a future research topic that merits closer examination, including whether diseases and pathogens infect meat and its nutritional status.